The Effect of Online Games on English Language Skills - Nurhaida Lakuana; Dwi Wahyu Dermawan Adam; ST. Marhana Rullu (BABASAL English Education Journal, 2023)
This study aims to determine the effect of online games on the English skills of students of the English Language Education Study Program at Muhammadiyah Luwuk University. This study used a qualitative approach as a research method, the subjects of this study were 10 active students of the English Language Education Study Program at Muhammadiyah Luwuk University. This research purpose is to find out the effect of online games on English skills. In order to analyze the data, the researchers conducted interviews and took notes from video game recordings. As a result of this research. Researchers found that online games have a significant effect on improving English language skills. The effect are students can learn and practice their English skills such as speaking, reading, listening, and writing skill. Therefore, students can improve their English skills because in the game participants can use this as a means of learning and practicing English skills.